Effective "activated PI3Kδ syndrome"-targeted therapy with the PI3Kδ inhibitor leniolisib - Rao, V Koneti; Webster, Sharon; Dalm, Virgil A S H; Šedivá, Anna; van Hagen, P Martin; Holland, Steven; Rosenzweig, Sergio D; Christ, Andreas D; Sloth, Birgitte; Cabanski, Maciej; Joshi, Aniket D; de Buck, Stefan; et al. (Blood, 2017)
Pathogenic gain-of-function variants in the genes encoding phosphoinositide 3-kinase δ (PI3Kδ) lead to accumulation of transitional B cells and senescent T cells, lymphadenopathy, and immune deficiency (activated PI3Kδ syndrome [APDS]). Knowing the genetic etiology of APDS afforded us the opportunity to explore PI3Kδ inhibition as a precision-medicine therapy. Here, we report in vitro and in vivo effects of inhibiting PI3Kδ in APDS. Treatment with leniolisib (CDZ173), a selective PI3Kδ inhibitor, caused dose-dependent suppression of PI3Kδ pathway hyperactivation (measured as phosphorylation of AKT/S6) in cell lines ectopically expressing APDS-causative p110δ variants and in T-cell blasts derived from patients. A clinical trial with 6 APDS patients was conducted as a 12-week, open-label, multisite, within-subject, dose-escalation study of oral leniolisib to assess safety, pharmacokinetics, and effects on lymphoproliferation and immune dysregulation. Oral leniolisib led to a dose-dependent reduction in PI3K/AKT pathway activity assessed ex vivo and improved immune dysregulation. We observed normalization of circulating transitional and naive B cells, reduction in PD-1+CD4+ and senescent CD57+CD4- T cells, and decreases in elevated serum immunoglobulin M and inflammatory markers including interferon γ, tumor necrosis factor, CXCL13, and CXCL10 with leniolisib therapy. After 12 weeks of treatment, all patients showed amelioration of lymphoproliferation with lymph node sizes and spleen volumes reduced by 39% (mean; range, 26%-57%) and 40% (mean; range, 13%-65%), respectively. Thus, leniolisib was well tolerated and improved laboratory and clinical parameters in APDS, supporting the specific inhibition of PI3Kδ as a promising new targeted therapy in APDS and other diseases characterized by overactivation of the PI3Kδ pathway. This trial was registered at www.clinicaltrials.gov as #NCT02435173.
Keywords: slezina; Dose-Response Relationship, Drug; Phenotype; demografie; ženské pohlaví; lidé; vztah mezi dávkou a účinkem léčiva; mutace; imunoglobulin M; Female; Class I Phosphatidylinositol 3-Kinases; Rats; Spleen; velikost orgánu; lymfatické uzliny; Pyridines; Child; předškolní dítě; Demography; Child, Preschool; chemokiny; Immunologic Deficiency Syndromes; Lymphocyte Activation; Animals; Protein Kinase Inhibitors; T-lymfocyty; Humans; fenotyp; Primary Immunodeficiency Diseases; TOR serin-threoninkinasy; T-Lymphocytes; pyridiny; zvířata; fosfatidylinositol-3-kinasy třídy I; Infant; cílená molekulární terapie; mužské pohlaví; TOR Serine-Threonine Kinases; Lymph Nodes; Mutation; Chemokines; Male; aktivace lymfocytů; primární imunodeficience; kojenec; krysa rodu Rattus; pyrimidiny; inhibitory proteinkinas; Organ Size; syndromy imunologické nedostatečnosti; Pyrimidines; Molecular Targeted Therapy; Transfection; transfekce; dítě; Immunoglobulin M